ECOOP 2011 object-oriented programming 25th European conference, Lancaster, Uk, July 25-29, 2011 proceedings - ECOOP 2011 2011 Lancaster, England); Mezini, Mira 1966-.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 25th European Conference on Object-Oriented Programming, ECOOP 2011, held in Lancaster, UK, in July 2011. The 26 revised full papers, presented together with three keynote lectures were carefully reviewed and selected from a total of 100 submissions. The papers cover topics such as empirical studies, mining, understanding, recommending, modularity, modelling and refactoring, aliasing and ownership; as well as memory optimizations.
Electronic reproduction.
Keywords: Object-oriented programming (Computer science) -- Congresses; Object-oriented methods (Computer science) -- Congresses; Electronic books